Quality of city life multiple criteria analysis. (February 2018) - Kaklauskas, A.; Zavadskas, E.K.; Radzeviciene, A.; Ubarte, I.; Podviezko, A.; Podvezko, V.; Kuzminske, A.; Banaitis, A.; Binkyte, A.; Bucinskas, V.
Abstract: International practice applies several urban indicators for sustainable cities (Monocle's Quality of Life Survey, Quality of Life Index (QLI), Indicators for Sustainability, European Green City Index, City Blueprint and others). These urban indicators can serve in performing integrated monitoring, assessing and recommending objectives sought by cities by different quantitative and qualitative aspects. Some of these tools can be applied to assessing a city's quality of life. One of the goals of this article is to compare several alternative methods for assessing a city's quality of life and their accuracies. A comparison was performed of the QLI and INVAR methods while conducting an analysis of comparable data from the 2012–2016 surveys on the Quality of Life in European Cities. Upon establishing the rankings of European cities by their quality of life with the assistance of the QLI and INVAR methods, an estimation of correspondence of results obtained by both methods and sensitivity analysis were performed based on a quantitative tool proposed in this paper. The obtained values of such criteria revealed a good level of congruity between the ranks obtained by employing both methods. The sensitivity analysis indicated that the results yielded by both the QLI and INVAR methods for rating the quality of life in European cities per the ever-fluctuating 2012–2016 data were similar. In other words, there was little difference between these methods for city ranking. This research also provides the INVAR method and its abilities to supplement the QLI with new functions: quantitative recommendations for cities under analysis by the indicators under analysis, optimization of indicators with consideration of indicators achieved in the quality of life area, and establishment of the values of the indicators under analysis permitting the city under analysis to raise its rating to the desired level. Highlights: There was low sensitivity to differences between the methods under analysis. INVAR method supplements Quality of Life Index technique with new functions. INVAR provides quantitative guidelines for improving the quality of life (QL) in cities. INVAR optimizes indicators by considering the existing QL situation in a city. INVAR identifies indicator values allowing the city to upgrade to a desired rating.